2014
DOI: 10.5897/ajmr2013.6257
|View full text |Cite
|
Sign up to set email alerts
|

The interactions between esp, fsr, gelE genes and biofilm formation and pfge analysis of clinical Enterococcus faecium strains

Abstract: Enterococcus faecium has become an increasingly important nosocomial pathogen due to formation of biofilms on several surfaces. Sixty one (61) E. faecium strains isolated from blood, urine and fecal were assessed for biofilm production, the effect of different glucose concentration on biofilm production and also the presence of esp, fsr and gelE genes. Pulsed field gel electrophoresis (PFGE) method was performed to show chromosomal similarities and also to determine correlation between biofilm formation abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
3
4
0
Order By: Relevance
“…A similar proportion was observed in Spain (75%) (Latasa et al, 2006). However, studies by other authors showed different results; in India, Italy, and Turkey, E. faecium isolates were able to produce biofilm less frequently or even could not form this structure (0%, 28.8%, and 48%, respectively) (Prakash et al, 2005;Di Rosa et al, 2006;Diani et al, 2014). These results indicate that the level of the ability to form biofilm among E. faecium, as well as the factors conducive to its formation, vary with geographic location.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…A similar proportion was observed in Spain (75%) (Latasa et al, 2006). However, studies by other authors showed different results; in India, Italy, and Turkey, E. faecium isolates were able to produce biofilm less frequently or even could not form this structure (0%, 28.8%, and 48%, respectively) (Prakash et al, 2005;Di Rosa et al, 2006;Diani et al, 2014). These results indicate that the level of the ability to form biofilm among E. faecium, as well as the factors conducive to its formation, vary with geographic location.…”
Section: Discussionsupporting
confidence: 54%
“…Despite the fact that the biofilm-formation process has an essential impact on the course of enterococcal infections, our knowledge of the mechanisms and factors involved in this process is still insufficient (Almohamad et al, 2014). Therefore, many studies have sought to find the relation between biofilm formation and virulence genes, especially esp and gelE, among Enterococcus (Dupre et al, 2003;Dworniczek et al, 2005;Raad et al, 2005;Di Rosa et al, 2006;Heikens et al, 2007;Fisher & Philips, 2009;Diani et al, 2014). We reported that the prevalence of esp gene was higher in BIO + isolates (71.4%) than in BIOstrains (55%), but that this difference was statistically insignificant, and that many esp-positive isolates did not form biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…E. faecalis is known to cause infections mainly due to the expression of virulence factors associated with adherence of mucosal and abiotic surfaces (1). The number of complete or draft genome sequences available for E. faecalis as of April 2017 is 503, comprising the bulk of enterococcal genome sequences available.…”
Section: Genome Announcementmentioning
confidence: 99%